Increased Dust Deposition in New Zealand Related to Twentieth Century Australian Land Use. Issue 5 (6th May 2019) - Brahney, Janice; Ballantyne, Ashley P.; Vandergoes, Marcus; Baisden, Troy; Neff, Jason C.
Abstract: Mineral aerosols (dust) generated in the dryland regions of Australia have the potential to reach New Zealand through atmospheric transport. Although a large portion of dust in New Zealand originates in Australia, little is known about how dust deposition has varied over time in New Zealand or what may have caused this variation. We used geochemical dust proxies to examine the recent history of dust deposition to two alpine lakes in Kahurangi National Park, South Island, New Zealand. Geochemical indicators suggest that dust deposition began to increase around 1900, with the greatest deposition rates occurring from ~1920 to ~1990. In subsequent decades, dust deposition rates to New Zealand lakes appear to have declined. This rise and fall of dust deposition recorded in New Zealand lakes is consistent with dust records from the Antarctic Ice Sheet, Eastern Australia, and incidents of low visibility due to dust events recorded at Australian climate stations. The dust deposition rate over time also follows the temporal pattern of land use in south and central Australia over the time scale of the twentieth century suggesting a causal linkage. It is possible, and perhaps likely, that drought cycles also affected both emissions and transport pathways but over shorter time periods this was difficult to discern at the temporal resolution of these lake sediment cores. The increase in dust deposition to the high‐elevation regions of New Zealand likely has implications for the biogeochemistry of alpine lakes in the Tasman Mountains. Key Points: Dust deposition in New Zealand increased in the twentieth century as compared to the last 2, 000 years Dust deposition decreased from 1990 AD to the present Reconstructed dust fluxes appear to vary in response to historical land use changes in Australia